2011
DOI: 10.1111/j.2044-8295.2011.02053.x
|View full text |Cite
|
Sign up to set email alerts
|

The neural processing of familiar and unfamiliar faces: A review and synopsis

Abstract: Familiar faces are represented with rich visual, semantic, and emotional codes that support nearly effortless perception and recognition of these faces. Unfamiliar faces pose a greater challenge to human perception and memory systems. The established behavioural disparities for familiar and unfamiliar faces undoubtedly stem from differences in the quality and nature of their underlying neural representations. In this review, our goal is to characterize what is known about the neural pathways that respond to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
137
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(156 citation statements)
references
References 66 publications
19
137
0
Order By: Relevance
“…The FRU is activated by any view of a face that is processed at earlier stages in the functional model as a structural code (Bruce & Young, 1986). Some studies have suggested differences in the neural representation of faces that are visually familiar only (e.g., images from magazines), versus those that are unknown, with greater activation to unfamiliar faces in early face regions of the cortex (e.g., Rossion, Schiltz, Robaye, Pirenne, & Crommelinck, 2001), although others reported no differences in face familiarity in face-selective regions (see Natu and O'Toole, 2011, for a review). Therefore, it is not sufficiently clear at what level repeated face images are processed during face perception, but it seems unlikely that repeated exposure to the same image of a (previously unfamiliar) face is sufficient to activate the PIN and more likely that activation occurs earlier in information processing such as the level of the FRU.…”
Section: Discussionmentioning
confidence: 99%
“…The FRU is activated by any view of a face that is processed at earlier stages in the functional model as a structural code (Bruce & Young, 1986). Some studies have suggested differences in the neural representation of faces that are visually familiar only (e.g., images from magazines), versus those that are unknown, with greater activation to unfamiliar faces in early face regions of the cortex (e.g., Rossion, Schiltz, Robaye, Pirenne, & Crommelinck, 2001), although others reported no differences in face familiarity in face-selective regions (see Natu and O'Toole, 2011, for a review). Therefore, it is not sufficiently clear at what level repeated face images are processed during face perception, but it seems unlikely that repeated exposure to the same image of a (previously unfamiliar) face is sufficient to activate the PIN and more likely that activation occurs earlier in information processing such as the level of the FRU.…”
Section: Discussionmentioning
confidence: 99%
“…These regions include the so-called "core face-processing system" (16), comprising regions in the middle section of the lateral fusiform gyrus ["fusiform face area" (FFA)], the lateral inferior occipital gyrus ["occipital face area" (OFA)], and the posterior superior temporal gyrus. However, these regions, which are identified with unfamiliar face stimuli, show only weak and/or inconsistent differences between familiar and unfamiliar faces (17). For example, within the right FFA, face familiarity has been associated with either increased or decreased neural activation (18,19).…”
mentioning
confidence: 97%
“…5 Face perception is a highly complex and sophisticated process underpinned by a distributed neural system that comprises several brain areas, including the fusiform gyrus, superior temporal sulcus (STS), insula, amygdala, and temporal poles. 6,7 Behavioral and neurobiological studies consistently suggest that such a system may be affected in SAD. [8][9][10] While a hyperreactivity in the amygdala has been a consistent finding across most studies on face perception in SAD (e.g.…”
Section: Introductionmentioning
confidence: 99%